The winners - Backman, Fredrik, 1981-; Smith, Neil (Neil Andrew) (London : Simon & Schuster Ltd, 2022)
The long-awaited conclusion to the beloved New York Times bestselling and 'engrossing' (People) Beartown series - which inspired an HBO series of the same name - follows the small hockey town's residents as they grapple with change, pain, hope, and redemption. Two years have passed since the events that no one wants to think about. Everyone has tried to move on, but there's something about this place that prevents it. The residents continue to grapple with life's big questions: What is a family? What is a community? And what, if anything, are we willing to sacrifice in order to protect them? As the locals of Beartown struggle to overcome the past, great change is on the horizon. Someone is coming home after a long time away. Someone will be laid to rest. Someone will fall in love, someone will try to fix their marriage, and someone will do anything to save their children. Someone will submit to hate, someone will fight, and someone will grab a gun and walk towards the ice rink. So what are the residents of Beartown willing to sacrifice for their home? Everything.
Originally published in Sweden as Vinnarna by Forum, 2021.
Translated from the Swedish.
Keywords: Beartown (Imaginary place) -- Fiction; Sweden -- Fiction; Sweden; Fiction; Fiction